Selection of broodstock of Tiger Prawn, penaeus monodon fabricius, on the basis of Morphometric traits - Daud, Siti Khalijah; Ang, K. J. (Universiti Putra Malaysia Press, 1995)
Mature Penaeus monodon were collected from Kedah, Perak, Terengganu, johore and Sabah waters in Malaysia. Selected morphometric characters and body weight Were measured individually. The results showed that the females were significantly larger (P<O.05) than the males in all locations. Stepwise regression analysis indicated that carapace length alone is sufficient to explain the variance in body weight for male and female prawns and can thus be used as a criterion for the selection of broadstock. The logarithmic relationships between body weight and total length. body weight and carapace length, and between carapace length and total length for both sexes were also calculated.